Konsep Tazkiyat Al-Nafs Dalam Al-Quran (Perspektif Tafsir MaqÄá¹£idi) - Mukhtar Syafangat; Muh Tasrif (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
Tazkiyat al-nafs is a process of improving the soul and purifying it through the way of knowledge (á¹alabul 'ilmi), doing good deeds, and doing Allah's commands and staying away from his prohibitions. Because the dimension of the soul in human life is very influential in fostering the faith, Islam, and ihsan of a Muslim. For this reason, the study aims to explain how the meaning of tazkiyat al-nafs in the Qur'an is, knowing how the steps taken by tazkiyat al-nafs according to the Qur'an. The type of research used is library research. In this discussion, the researcher focuses on the application of the maqÄá¹£idi aspect to explore the meaning of the verses about tazkiyat al-nafs and explain the meaning of the commandment of tazkiyat al-nafs in the Qur'an. This study uses the maudhu'i interpretation method. The results of this study are first, tazkiyat al-nafs in the Qur'an contains the meaning of making sustenance useful and blessing for the human soul, giving pious and pious offspring that bring benefits, fostering trustworthy behavior in humans. Second, the steps of tazkiyat al-nafs according to the Qur'an are seeking knowledge, doing business. and choose halal and good food.